2009
DOI: 10.1038/onc.2009.24
|View full text |Cite
|
Sign up to set email alerts
|

RanBP1 downregulation sensitizes cancer cells to taxol in a caspase-3-dependent manner

Abstract: Mitotic microtubule (MT)-targeting drugs are widely used to treat cancer. The GTPase Ran regulates multiple processes, including mitotic spindle assembly, spindle pole formation and MT dynamics; Ran activity is therefore essential to formation of a functional mitotic apparatus. The RanBP1 protein, which binds Ran and regulates its interaction with effectors, is overexpressed in many cancer types. Several observations indicate that RanBP1 contributes to regulate the function of the mitotic apparatus: RanBP1 ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 65 publications
2
33
0
Order By: Relevance
“…A variety of cell death phenomena have been associated with paclitaxel, ranging from interrupting microtubule dynamics to cell cycle arrest at the G2/M phase and promoting the serial cleavage events of apoptotic effector caspases (CASPs), such as caspase-10, -8, -7, and -3 [68,69,70]. A report suggested that paclitaxel sensitivity has a positive correlation with USP15 protein expression in HeLa cells, and that the binding of procaspase-3 with the components of SCF (Skp1-CUL1-F-box) may be controlled by USP15.…”
Section: Acquired Chemoresistance Of Cancer Cellsmentioning
confidence: 99%
“…A variety of cell death phenomena have been associated with paclitaxel, ranging from interrupting microtubule dynamics to cell cycle arrest at the G2/M phase and promoting the serial cleavage events of apoptotic effector caspases (CASPs), such as caspase-10, -8, -7, and -3 [68,69,70]. A report suggested that paclitaxel sensitivity has a positive correlation with USP15 protein expression in HeLa cells, and that the binding of procaspase-3 with the components of SCF (Skp1-CUL1-F-box) may be controlled by USP15.…”
Section: Acquired Chemoresistance Of Cancer Cellsmentioning
confidence: 99%
“…The finding that RanBP1 abundance is critical for mitotic MT function opens a new issue, raising the possibility that it may influence the efficacy of MT-targeting chemotherapeutic drugs when deregulated in cancer cells. Indeed, RanBP1 silencing increased the sensitivity of transformed cells to taxol [47]; retrospectively, this can account for the observed paclitaxel resistance in RanBP1-overexpressing breast cancers (http://www.ncbi.nlm.nih.gov/geo; see RanBP1 in dataset record GDS360). Therefore, in a newly emerging scenario, RanGTP activity can amplify or antagonize the effect, and hence the therapeutic outcome, of MT-targeting drugs in cancer cells.…”
Section: Ranbp1 Regulates a Subset Of Mt-associated Factorsmentioning
confidence: 99%
“…First, the expression profile of genes encoding MT-associated and MT-regulatory proteins found in different cancer types, and also within cells from a same cancer, can synergize with, or antagonize, the effect of the drugs [1214]. Second, tumor cells can develop resistance through diverse mechanisms [4, 1517], involving not only the induction of efflux pump mechanisms implicated in multidrug resistance, but also the presence of mutations or differential expression of tubulin isotypes [1821].…”
Section: Introductionmentioning
confidence: 99%